Colliding Epistemologies: Reflections on Nidhal Guessoum - Lohlker, Rüdiger (Interdisciplinary journal for religion and transformation in contemporary society, 2021)
Modern sciences and Islam are oftentimes perceived (or presented) as irreconcilable or even as mutually exclusive poles. In attempting to re-establish the dialogue on the topic and to find contemporary approaches that might enable one to keep personal religious beliefs while also engaging with modern sciences, this article discusses the works of contemporary physicist Nidhal Guessoum. Guessoum not only critically examines current developments in the realm of science in the Muslim world, but also provides the reader with a solution to what seems to be a problem of colliding epistemologies: reconciling the two traditions. According to Guessoum, both traditions – although using different methods – work towards advancing knowledge and should thus both be upheld and progressed. To illustrate his approach to scientific methodology and thinking, the article also provides an analysis of Guessoum’s videos on COVID-19 and thereby addresses a current topic which clearly proves the need for reliable modern science.